2008
DOI: 10.1016/j.cognition.2007.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Children’s understanding of the relationship between addition and subtraction

Abstract: In learning mathematics, children must master fundamental logical relationships, including the inverse relationship between addition and subtraction. At the start of elementary school, children lack generalized understanding of this relationship in the context of exact arithmetic problems: they fail to judge, for example, that 12 + 9 − 9 yields 12. Here, we investigate whether preschool children's approximate number knowledge nevertheless supports understanding of this relationship. Five-yearold children were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
2
35
1
Order By: Relevance
“…Studies on preschoolers have shown that formal instruction is not necessary to understand the inversion concept, although not all children demonstrate understanding (e.g., Baroody & Lai, 2007;Gilmore & Spelke, 2008;Klein & Bisanz, 2000;Sherman & Bisanz, 2007). A number of studies have also examined school-aged children's understanding of the concept (e.g., Bryant, Christie, & Rendu, 1999;Gilmore, 2006;Gilmore & Bryant, 2006;Robinson et al, 2006;Siegler & Stern, 1998;Stern, 1992).…”
Section: The Inversion Conceptmentioning
confidence: 96%
“…Studies on preschoolers have shown that formal instruction is not necessary to understand the inversion concept, although not all children demonstrate understanding (e.g., Baroody & Lai, 2007;Gilmore & Spelke, 2008;Klein & Bisanz, 2000;Sherman & Bisanz, 2007). A number of studies have also examined school-aged children's understanding of the concept (e.g., Bryant, Christie, & Rendu, 1999;Gilmore, 2006;Gilmore & Bryant, 2006;Robinson et al, 2006;Siegler & Stern, 1998;Stern, 1992).…”
Section: The Inversion Conceptmentioning
confidence: 96%
“…Recent evidence also suggests that a system of approximate non-symbolic representation of number may play a role in children's developing understanding of quantitative inversion. Five-year-old children can identify and use inverse relationships for large numbers with approximate symbolic or nonsymbolic (dot array) quantities before they can do so for exact symbolic quantities (Gilmore & Spelke, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although several other studies demonstrate that children between 4 and 9 years of age perform better on inversion problems such as a + b À b than on control problems such as a + b À c, these have involved children who were already receiving formal instruction in arithmetic (Gilmore & Bryant, 2008;Rasmussen, Ho, & Bisanz, 2003). More recently, 5½-year-old preschoolers were shown to perform better on inverse problems than on control problems on approximate nonsymbolic tasks with large sets (Gilmore & Spelke, 2008), like those used in the current study, as well as on symbolic tasks with large sets. Together with the current results, this pattern suggests that children may gradually come to understand the conceptual nature of inversion with large sets between 3½ and 5½ years of age.…”
Section: Discussionmentioning
confidence: 95%
“…First, it contributes to scientific understanding about the nature of the number sense that humans share with other animals before humans' ability to learn symbolic mathematics sets them apart. Second, it contributes to the literature on the development of knowledge about the mathematical principle of inversion-that addition and subtraction are inversely related and, thus, cancel each other out (e.g., Gilmore & Spelke, 2008). Finally, the answer to this question has educational implications.…”
Section: Preschoolers' Nonsymbolic Arithmetic With Large Setsmentioning
confidence: 95%